CLASSROOM ASSESSMENT PRACTICES: AN EVALUATION OF BASIC EDUCATION SCHOOL TEACHERS - Yar Zar Chit; Lu San (lppm Universitas Negeri Jakarta, 2022)
This study aimed to investigate the classroom assessment practices of teachers in Myitkyina Township, Myanmar. A total of 237 teachers from Basic Education High Schools in Myitkyina Township participated in this study. Descriptive research design and survey method were used.  An instrument: Teachers' Classroom Assessment Practices Questionnaire was used to collect the required data. The internal consistency was =0.87. According to the results, the sample mean (193.22) is larger than the theoretical mean (141). Then, it was found that there were significant differences in teachers' using performance assessment and non-achievement-based grading by gender. Similarly, in the comparison of teachers' assessment practices by subject, mean score of science teachers was highest and that of art teachers was lowest. Moreover, in the comparison of teachers' assessment practices by position, mean score of senior teachers was highest and that of primary teachers was lowest in assessment practices.  Similarly, in the comparison of teachers' assessment practices by service, mean score of teachers who have above 30-year service was highest. Finally, this study hopes that the school administrators can get the ideas to recover and promote the teachers' classroom assessment practices with the cooperation of the experts.